NUCLEAR IMAGING IN PULMONARY HYPERTENSION - V. B. Sergienko; E. G. Valeeva (Евразийский Кардиологический Журнал)
The review describes current possibilities of nuclear imaging methods in different types of pulmonary hypertension (PH): lung ventilation-perfusion scintigraphy and single photon emission computed tomography (SPECT), radionuclide ventriculography and angiography, as well as new potentials of myocardial perfusion SPECT for the evaluation of right ventricle.